Wychowanie obywatelskie w katechezie - Kazimierz Nycz (Jesuit University Ignatianum in Krakow, 2017)
The very topic of the article Civic Education in Catechesis may create controversy. Through the years of the communist system in power, there was a subject at schools - civic education - everybody knows what it taught. At present, this issue, according to many, is reserved for school teaching and education. Yet, the documents of the Church since the Vatican Council (Gaudium et spes), through the adhortation Christifideles laici, up to the Catechism of the Catholic Church and the latest catechetic documents, incessantly indicate the necessity to take up issues regarding educating social attitudes, also on the grounds of catechesis, in cooperation with the family, school and organisations of social life. Also, catechesis of the Church in Poland does not fear facing this new reality, postulated by the documents of the general Church and the Church in Poland. Civic education is possible and desirable in the present situation of the country, in which everybody needs to be taught how to live in democracy. The analyses presented in the article show that a lot has been done on the level of catechetic syllabuses, textbooks and catechesis. It means performing complementary function towards civic education at school, as well as serving own catechetic function. It is also didactic-educational cooperation through correlation with school subjects and educational paths. The integrity of civic formation must consist in levelling the discrepancy between faith and life, "spiritual world" and "secular world". There is still a lot to do in this matter, in schools, parishes and, especially, in catechesis for adults. Civic education should be conducted by competent people, critically perceiving the world and its problems, but seeing hope